SCHOLARLY PUBLICATION: Editorial constraints versus NNS strategies - SLOUGUI, Doudja (Journal of Human Sciences, 2015)
The issue of scholarly publications written by Non-Native Speakers (henceforth NNS) has, over the last decade, attracted the interest and concern of a great number of researchers. They have sought to find out the reasons that lie behind the rejection of papers by academic journals and editorial boards. These range from an editorial prejudice from the North towards the South, to a linguistic bias against non-English Speakers. Despite the many difficulties which NNS scientists encounter, a few manage to carve their way into this closed world of research. The purpose of this paper is to describe the strategies which have helped Algerian scientists to acquire membership in the field of scholarly publication. Using a qualitative methodology (verbal accounts as well as written records), the research examines how Non-English Speaking scientists negotiate their contributions into peer-refereed English journals, and how the international audience responds to their submissions.